Gender inequality in the South African labour market: Insights from the Employment Equity Act data. Issue 4 (2nd October 2019) - Espi, Gabriel; Francis, David; Valodia, Imraan
Abstract: In the years following the end of Apartheid, South Africa introduced the Employment Equity Act as part of legislation designed to address entrenched racial and gender inequalities. Through section 27 of the Act, firms are required to report on the representation and remuneration of their workers by gender and population group. In this study, unprecedented access to the data generated by this reporting was used to assess gender-based occupational segregation and pay gaps in 2015 and 2016. We found the data on employment to be relatively trustworthy and to show that women (and especially black and coloured women) continue to be under-represented in high-skilled and management positions. Substantial gender pay gaps were found, but the reliability of these estimates was made questionable by a high number of apparent errors and inconsistencies in the remuneration data. The data has several advantages over other household and firm surveys, but these issues undermine its potential for the estimation of gender pay gaps among workers matched on occupational skill levels. This analysis shows that more needs to be done to ensure that this data is appropriately processed and distributed, so that it can shed light on the state of women in the South African labour market and be used to effectively address inequalities in pay and representation.